Evidence-based mixture containing Lactobacillus strains and lactoferrin to prevent recurrent bacterial vaginosis: a double blind, placebo controlled, randomised clinical trial. - Russo, R; Karadja, E; De Seta, F (Benef Microbes, 2019)
Bacterial vaginosis (BV) is the most common cause of vaginal discomfort in women. It is characterised by abnormal vaginal microbiota with a depletion of lactobacilli and predominance of anaerobic microorganisms, mainly Gardnerella vaginalis and Atopobium vaginae. Although antibiotics represent an effective therapeutic option in the short-term, recurrent infections still remain a serious problem. Nowadays, evidence exists about the efficacy of probiotics for the management of BV. The aim of the current double blind, randomised clinical trial was to assess the efficacy of a probiotic mixture, including Lactobacillus acidophilus GLA-14 and Lactobacillus rhamnosus HN001, in combination with bovine lactoferrin, as adjuvant therapy to metronidazole in women with recurrent BV. In particular, normalisation of Nugent score, remission of symptoms and recurrences during a six-months follow-up were assessed. 48 adult women received metronidazole (500 mg twice daily) for 7 days and randomly assigned to take simultaneously either probiotics plus lactoferrin or placebo (2 capsules/day for 5 days followed by 1 capsule/day for 10 consecutive days; induction phase). The verum or placebo administration (1 capsule/day for 10 consecutive days) was repeated each month (maintenance phase) during the six months of follow-up starting the first day of menstrual cycle since the menstrual blood increases the vaginal pH and contributes to increase the risk of recurrences. The results showed that symptoms (vaginal discharge and itching), Nugent score and recurrence rate were significantly improved by probiotics mixture in association with lactoferrin. This alternative approach may represent a safe and effective remedy for the restoration of healthy vaginal microbiota in preventing recurrent BV.